The Rowan Tree Church 1995-1996 Annual Report - Rowan Tree Church (Kirkland: WA: Rowan Tree Church, 1995)
The fourteenth annual reports contains exciting news regarding the donation of an acre of land to Rowan Tree Church by the Revs. Paul and gerry Beyerl. Other points of interest is the transfer of RT News responsibility of the Vice President of the Board of Directors, Rev. Ron Weroski of Ontario, Canada and the use of technology to transmit documents, specifically the Fax machine. The Prison Outreach Program provides insight to the issues prisoners face in receiving material.
This digital asset was created from the original digital scans by Rev. Paul V. Beyerl and provided to the Valdosta State University, Archives & Special Collections to be part of their Rowan Tree Church Periodicals Collection of the New Age Movements, Occultism, and Spiritualism Research Library. The Rowan Tree Church is an earth-based religion founded by Rev. Paul Beyerl, a Third Degree Initiate in the Alexandrian Tradition of Wicca, and incorporated on February 4, 1980 in Minneapolis, Minnesota. The church is now based in Kirkland, Washington with many communities throughout the United States and Canada. The roots of the Church extend back to 1976 which Rev. Beyerl began teaching Wicca, Astrology, and Herbalism out of his home. The Church's religion, The Tradition of Lothloriën, embraces inclusiveness and accepts all people regardless of faith, sexual orientation, race, or gender, a noted departure from early Alexandrian Wicca. The Tradition has elements of Herbalism, Astrology and Tibetan Buddhism in its structure, and is deeply rooted in its Mystery School, an in-depth study program that leads to Ordination, and the Hermit's Grove, its educational and publishing entity. Noted publications are The Unicorn, The Littlest Unicorn for children, and The Hermit’s Lantern.
Keywords: Rowan Tree Church--History; Rowan Tree Church--Appropriations and expenditures; Lothloriën (Wiccan sect); Mystery School of Lothloriën; Wicca--Study and teaching; Church work with prisoners; Prisoners--Religious life; Galadhrim Society.; Prison Outreach Program.; Annual reports.